Footwear Sectoral Analysis : Nepal - World Bank (World Bank, Washington, DC, 2019)
Nepal’s footwear industry is small but growing, and has been identified as a priority export sector by the government.Nepal’s footwear industry is a relatively small export industry, accounting for just 1.5 percent of the country’s total exports in 2017. Similar to other light manufacturing sectors, Nepal’s wage advantage in footwear is offset by its low firm-level productivity. Most firms have poor bookkeeping and a lack of accounting. Production facilities are ill-suited for manufacturing and distribution, and conditions in many factories are poor, sometimes dangerous. Nepali footwear manufacturers need to start by improving basic organizational and management skills. There is a dearth of industry-ready education and skills, and an unavailability of trained manpower that impedes investment from both domestic and foreign companies in these sectors. It is pertinent to focus on basic requirements such as education and skills development to increase the pool of skilled manpower in the country across sectors. Developing capabilities in Nepal’s small and medium-sized footwear manufacturers requires investment in improving managerial skills, upgrading quality standards, and modernizing production facilities to become safer and more efficient. The government of Nepal can help the domestic footwear industry by providing a vibrant trade policy to allow for deeper integration into regional value chains, opening up opportunities for foreign direct investment (FDI), and substantially improving the investment climate.